Evaluating the effect of using augmented reality (Metaverse) on improving the teaching and academic performance - AL-Tkhayneh, Khawlah Mitib; Ellala, Ziyad Kamel; Abuawad, Balkees; Alkhatib, Razan; Almasri, Eman Saleh (Edelweiss Applied Science and Technology, 2024)
This study aimed at evaluating the effect of employing the augmented reality (metaverse) on improving the process of teaching and academic performance. An electronic questionnaire containing five questions was distributed to the academic groups that received the lesson using augmented virtual reality (Metaverse). The aim of the questions was to evaluate their experience, and after they answered the questions, the answers were analyzed in the form of percentages and frequencies. The study sample consisted of (97) students from Al-Ain University enrolled in the programs of (special education, nutrition, and applied sociology), to whom the experiment was applied using augmented virtual reality in teaching during their academic course. The results revealed that (83%) of the respondents reported that the augmented virtual reality contributed to understanding the concepts of the lesson well, (79%) felt enjoyment in using this technique, (75%) suggested that the technique enhanced their involvement in the content well, (68%) suggested that augmented virtual reality could be a useful educational instrument in the future, and (77%) confirmed that the lesson’s objectives were achieved by using metaverse technique in teaching. However, several challenges were faced by students, including the used language (only English) and the negative effects of bad quality of used glasses. Based on the findings, the study recommended addressing several key areas for optimizing the use of augmented virtual reality (AVR) in teaching. For example, diversifying language options for AVR content is crucial to accommodating the linguistic diversity among students, thereby enhancing accessibility and comprehension. Additionally, we should invest in high-quality equipment and implement regular maintenance protocols to enhance the quality of equipment, specifically addressing issues related to the negative effects of subpar AVR hardware.